2006
DOI: 10.1002/humu.9471
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite in the 3′ untranslated region of human fibroblast growth factor 9 (FGF9) gene exhibits pleiotropic effect on modulating FGF9 protein expression

Abstract: Fibroblast growth factor 9 (FGF9) is a member of secreted polypeptide families and involved in many important biological processes, including implantation and morphogenesis during embryogenesis and adult life. Recently, Fgf9-knockout mice exhibited male-to-female sex reversal, demonstrating a novel function for FGF9 in testicular development. We hypothesized that FGF9 is involved in sex development at an early embryonic stage in humans. In this study, we systematically screened sequences of the FGF9 gene in 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 46 publications
1
40
0
Order By: Relevance
“…Similarly, if our 3 0 polymorphism were functional and in weak linkage disequilibrium or linkage equilibrium with SNPs examined in other studies, the association we found with mammographic density may be either stronger or only detectable in our study. Functional significance has been demonstrated for some microsatellites in non-coding regions, including the 3 0 untranslated region [44]. However, we have no evidence that our 3 0 polymorphism is functional, and its association with mammographic density still needs to be confirmed.…”
Section: Discussionmentioning
confidence: 81%
“…Similarly, if our 3 0 polymorphism were functional and in weak linkage disequilibrium or linkage equilibrium with SNPs examined in other studies, the association we found with mammographic density may be either stronger or only detectable in our study. Functional significance has been demonstrated for some microsatellites in non-coding regions, including the 3 0 untranslated region [44]. However, we have no evidence that our 3 0 polymorphism is functional, and its association with mammographic density still needs to be confirmed.…”
Section: Discussionmentioning
confidence: 81%
“…Experimental assays indicate that for some dinucleotide repeat variants in the promoter and other non-coding regions, alleles of different length influence transcription activity of specific genes [36][37][38], although there are no studies that indicate that the IGF1 promoter region 5 0 CA has functional effects. Associations between specific allele length groupings and breast cancer risk could also occur because of linkage disequilibrium between alleles within a grouping and an ungenotyped polymorphism that influences risk.…”
Section: Discussionmentioning
confidence: 99%
“…They identified four different alleles, (TG 13e16 ) (c.*275TG)n. The (TG) 14 motif was identified in their patients with 46,XY DSD of different aetiologies and rarely in controls (P ¼ 0.01). Functional studies demonstrated that the (TG) 14 allele had the greatest promoter activity in luciferase expression assays and also longer mRNA stability than the other alleles [17].…”
Section: Discussionmentioning
confidence: 99%
“…The region from c.*127 to c.*395 (from 932 to 1199 bp relative to the transcription start site of FGF9), was amplified and sequenced as described by Chen et al [17].…”
Section: Dmrt1 and Fgf9 Direct Sequencingmentioning
confidence: 99%